Factors Influencing Students' Enrollment in Health Science Majors at Higher Education Institutions in Phnom Penh, Cambodia - Sorn, Virak; Saut, Sopheakpanha; Suon, Monirath; Mao, Romnea; Lorn, Sokchan; Eat, Sokhoeun; Muk, Lykeang; Chhon, Yanvary (MASI Mandiri Edukasi, 2024)
Health science is crucial for a country's development. It provides healthcare knowledge and skills to health professionals to maintain the quality of health and well-being of its people. Cambodia's healthcare professionals are underrepresented in GDP growth because few students are interested in the health sciences. This study explores factors influencing students' decisions in choosing a health science major in higher education in Cambodia. It is a mixed-method study. Data was collected from the anonymous Google form questionnaire and focus-group discussions (FGDs). The quantitative data were analyzed using SPSS, while the qualitative data were analyzed thematically. The findings showed that tuition fees (38%), specialization courses offered (38%), university modern technology (31.4%), family's decision (29.8%), scholarship opportunity (29.8%), and university locations (24.8%), were the main factors for the participants' choices of their university majors. The theme-based results classified the students' decisions on health science majors into life experiences, role models, family support and engagement, academic performance, and career goals. The results further demonstrated that families, university profiles, and student academic performance played the most important roles in encouraging students' enrollment in health science majors to maintain the quality of the healthcare sector in Cambodia.